Investigations on the presence of e. coli o157: h7 in İnegöl and hamburger meat balls - Abdullah Keleş; Gürkan Uçar; Ahmet Güner (Eurasian Journal of Veterinary Sciences)
In this study, totally 41 minced meat, 32 hamburger balls (7 refrigerated. 25 frozen) and 46 Inagol meat balls (29 refrigerated. 17 frozen) were investigated for contamination of E. coli0157:H7, total mesophilic aerobic and coliform bacteria. One sample of minced meat (2.43%), 3 samples of refrigerated Inegot meat balls (10.34%), 1 sample of frozen Inegol meat balls (5,88%) and 3 samples of frozen hamburger balls (12%) were positive for E. coli 0157 serotype. E. coli 0157 serotype was not detected in refrigerated hamburger balls. And also H7 serotype was not detected in all E. coli 0157 positive samples. TMA counts of Inegol meat balls were 1.57x107 for refrigerated samples and 7.4x106 cfu/g for frozen samples. TMA counts of hamburger balls were found as 3.1X106 for frozen samples and 3,3x106 for refrigerated samples. Counts of coliform bacteria and coliform contaminated samples in Inegol meat balls were found higher than minced meat and hamburger ball samples. As a result, although E. coli 0157:H7 was not detected in all samples, E C0//O157 serotype was found as 8.69% for Inego! meat balls, 9.37% for hamburger balls and 2.43% for minced meat samples. Higher coliform bacteria contamination of Inegol meat balls and hamburger samples than minced meat and highest microbiological counts in Inegol meat balls show that hygienic conditions were low in the production of these meat products.